Both species richness and growth forms affect nutrient removal in constructed wetlands: A mesocosm experiment - Luo, Yumei; Chen, Quan; Liu, Fan; Dai, Can (Frontiers in Ecology and Evolution, 2023)
Plant richness is thought to improve the function of constructed wetlands (CWs), but most CWs are planted with monocultures, with only a few employed polycultures, which have drawn contradictory conclusions. We suppose functional diversity is the key to better performance of plant communities and hypothesize that CWs planted with diverse growth forms are superior in plant growth and nutrient removal. Six emergent plant species categorized into slender type (Schoenoplectus tabernaemontani, Typha orientalis), fan type (Iris sibirica, Acorus calamus) and large type (Canna indica and Thalia dealbata) were planted in monocultures, combinations (two species of the same growth form) and mixed polycultures (six species of three growth forms). We then compared how plant growth and nutrient uptake differed among treatments. Results showed that the polyculture considerably increased the removal of total nitrogen (TN) and total phosphorus (TP), but the combination did not outperform monoculture. High consistency in the patterns between underground biomass and total biomass indicated that plant roots were essential for nutrient consumption. Compared with slender and fan plants, the large plants had a greater biomass increase in polycultures, which greatly accelerated the absorption and assimilation of TN and TP. Our study indicated that plant community with various growth forms reduced the intensity of interspecific competition, increased the functional diversity, and greatly enhanced the ability of pollutant removal. Our results also provide some suggestions for plant selection and combination designs in CWs.